Perceived psychological stress and risk of herpes zoster: a nationwide population‐based cohort study. (1st July 2021) - Schmidt, S.A.J.; Sørensen, H.T.; Langan, S.M.; Vestergaard, M.
Summary: Background: Psychological stress may reduce cellular immunity, but its role in triggering latent infections, including herpes zoster (HZ), is controversial. Objectives: To examine the association between perceived psychological stress and risk of HZ. Methods: In a linked registry‐based cohort study, we followed 77 310 persons aged 40 years or older who participated in the 2010 Danish National Health Survey from 1 May 2010 until HZ diagnosis, death, emigration or 1 July 2014, whichever occurred first. We computed hazard ratios (HRs) of HZ associated with Cohen's Perceived Stress Scale (PSS) score (range 0–40) using Cox regression with age as the timescale, adjusted for sex, immunosuppressive and selected chronic conditions, immunosuppressive drugs, and sociodemographic, lifestyle and anthropometric factors. The PSS measures chronic stress perceived by an individual in response to various demands of daily life. We modelled the PSS score using quintiles and a restricted cubic spline function. Results: The unadjusted rate of HZ varied from 5·53 to 7·20 per 1000 person‐years from the lowest to the highest PSS score quintile. Compared with the lowest PSS score quintile, the adjusted HR for HZ was 1·00 [95% confidence interval (CI) 0·86–1·16], 1·08 (95% CI 0·92–1·26), 1·05 (95% CI 0·90–1·23) and 1·14 (95% CI 0·97–1·34) for the second to the fifth quintile, respectively. In cubic spline analyses, PSS scores < 20 were not associated with increased HR of HZ, but thereafter the HR increased linearly from 1·10 (95% CI 0·85–1·41) to 2·22 (95% CI 1·32–3·75). Conclusions: Our study indicated that high levels of psychological stress are associated with increased risk of HZ.